14x+12y+7 This expression cannot be simplified any further.
The given expression can be simplified to: x-12y
The given expression can be simplified to: x-12y
18x +12y = 0
Turn into y = mx + b form6x-12y = 24-12y = 24-6xy = 1/2x -2m = slope = 1/2
It is: 12x/6xy = 2/y simplified
2xy + 6xy = 8xy
Totally pointless
To simplify the expression 2x + 3y + 4x + 9y, you first combine like terms. Adding the coefficients of x terms gives 2x + 4x = 6x. Similarly, adding the coefficients of y terms gives 3y + 9y = 12y. Therefore, the simplified expression is 6x + 12y.
12y + 5 = 53 12y = 48 y = 4
The given equation: =3x-4x plus 9xy-12y =3x-4x+9xy-12y =-x+9xy-12y =-x+3y(3y-4) Answer.
5*3y+1+12y-1 = 15y+1+12y-1 = 27y.